Does Money Matter in Canada? Evidence from a Vector Error Correction Model - Ambler, Steve (The Review of Economics and Statistics, 1989)
This paper investigates the statistical properties of a set of Canadian and U.S. economic time series and uses the data to address the question of the importance of monetary variables in Canadian business cycle fluctuations. The individual time series are found to contain unit roots, but the data reveal the existence of several economically meaningful cointegrating vectors. A multivariate vector error correction model is estimated, and Canadian velocity, which appears as an error correction term, is significant in the Canadian output equation. This supports the contention that monetary variables have predictive content for real output. Copyright 1989 by MIT Press.